GEN Z DOOM SPENDING LIFESTYLE THAT INFLUENCES IMPULSIVE CONSUMER SHOPPING BEHAVIOR - Simatupang, Sudung; Butarbutar, Marisi; Susanti, Desi; Putri, Debi Eka (SULTANIST: Jurnal Manajemen dan Keuangan, 2025)
Changes in consumer behavior from generation Z today have experienced a significant shift to impulsive buying behavior and led to doom spending. The purpose of this study is to determine the impulsive behavior influenced by generation Z's lifestyle. The results found that all lifestyle and consumer behavior research variables have valid and reliable criteria. The regression equation used is a simple regression where the equation results are Y = 13.175 + 0.517X, From the results of this equation the correlation coefficient of lifestyle on impulsive consumer behavior has a positive contribution, this means that if the correlation coefficient shows a positive contribution, it means that there is a unidirectional relationship between lifestyle and impulsive consumption behavior. Then the partial hypothesis results show that there is a positive and significant effect on impulsive buying consumer behavior. This means that when lifestyle increases, impulsive buying consumer behavior will also increase.Keywords: Lifestyle, Doom Spending, Impulse Buying